Security in Society and Trying to Root it "Sociological Analytical Study" - دلالة, ميرنا (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research is an attempts for studying security considering it as an phenomenon in society, which must be focused on, and work on the application of sociological analysis tools for research and study.Especially as security-related problems and concerns become an integral part of our lives at the individual and collective levels, which also influence the shaping of social relations, whether through discourse or practice.Therefore, the primary objective of the research is to gather all the data related to the general dimensions of what we can call sociology of security; to deal with security as a basic social process, subject to change, without which human life can become in danger.